2020
DOI: 10.1080/09638288.2020.1762770
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the experiences, thoughts, and feelings underlying and influencing prehabilitation among cancer patients: a qualitative perspective on the what, when, where, who, and why

Abstract: To investigate the experiences, thoughts, and feelings that underlie and influence prehabilitation among cancer patients due to undergo major abdominal surgery. Materials and methodsPrior to their surgery, sixteen patients with peritoneal carcinomatosis of colorectal or ovarian origin due to undergo major surgery received oral information and a leaflet with preoperative recommendations. They subsequently participated in individual, semi-structured interviews.Malterud's principles of systematic text condensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 24 publications
3
48
0
Order By: Relevance
“…Patients stated that it was important for them to have a patient-centered program and that they can do what suits their individual situation. This was also found in another qualitative study on prehabilitation among abdominal cancer patients [30] and corresponds to the concept of a biopsychosocial health care model in which psychological, social, and medical issues interact [18].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Patients stated that it was important for them to have a patient-centered program and that they can do what suits their individual situation. This was also found in another qualitative study on prehabilitation among abdominal cancer patients [30] and corresponds to the concept of a biopsychosocial health care model in which psychological, social, and medical issues interact [18].…”
Section: Discussionsupporting
confidence: 68%
“…This statement is supported by a qualitative study among patients who were scheduled for major abdominal surgery (including for ovarian cancer). In that study, all patients received a leaflet with preoperative recommendations about preparation for surgery (among others about exercising, nutrition, relaxation, intoxications) [30]. Patients actually did put an extra effort into preparing themselves, as they became aware of the small actions they could do that could be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Only 37 of the 110 studies of prehabilitation had a nutrition treatment component. The study designs were as follows: 27% (n = 10) were protocols (18-27), 14% (n = 5) were pilot studies (8, 28-31), 5% (n = 2) were descriptions of prehabilitation programs (32, 33), 3% (n = 1) were case reports (34), 3% (n = 1) were feasibility studies (35), and 3% were qualitative studies (36). Of these 37 studies, 30% (n = 11) were cohort studies (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) and 16% (n = 6) were RCTs (48)(49)(50)(51)(52)(53).…”
Section: Prehabilitation Studies With a Nutrition Treatment Componentmentioning
confidence: 99%
“…Seventy-eight percent (n = 29) of the 37 identified studies included a statement regarding the conduct of nutritional assessment [n = 8 studies did not include a nutritional assessment statement (20,26,32,36,39,43,45,47)]; however, the application of assessment was inconsistent across studies. Eight percent (n = 3) of studies stated that an assessment was conducted without providing details of the method or tool used (21,25,42).…”
Section: Nutritional Assessment Within Prehabilitationmentioning
confidence: 99%
“…Studies on patient adherence to prehabilitation have shown the need to make the programs patientcentred by taking personal thoughts, needs and abilities into account [14][15][16], and practical barriers and facilitators should be considered [14,17]. Patients with depressive symptoms have been shown to bene t from prehabilitation interventions [18].…”
Section: Introductionmentioning
confidence: 99%